2011
DOI: 10.22201/ib.20078706e.2011.4.750
|View full text |Cite
|
Sign up to set email alerts
|

Patrones biogeográficos de los tenebriónidos epigeos (Coleoptera: Tenebrionidae) del Área Natural Protegida Península Valdés, Argentina: implicaciones para su conservación

Abstract: Resumen. Se realizó un estudio sobre los patrones biogeográficos de los tenebriónidos epigeos (Coleoptera: Tenebrionidae) que habitan el Área Natural Protegida Península Valdés (Chubut, Argentina), basado en datos de colecciones y material recolectado en viajes a la zona. Se presenta una lista exhaustiva de las especies en la que se consigna el grado de adaptación a la aridez de cada una de ellas; un análisis de la calidad del inventario y la estimación de la riqueza total de especies; una evaluación de los pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 38 publications
4
17
1
5
Order By: Relevance
“…Considering the species list, it was possible to recognize that 98% of species belong to the tribes Scotobiini, Nycteliini and Praociini. This result coincides with that of Kuschel (1969), who identified these tribes as the most representative of the Patagonian steppe, and with those of Sackmann and Flores (2009) and Carrara et al (2011a) who found the dominance of species of these three tribes for small-scale studies within the steppe. The high occurrence of endemic tenebrionids in the Patagonian steppe compared with other close arid biogeographic provinces suggests a role of its environmental history as the primary cause.…”
Section: Endemic Tenebrionids From the Patagonian Steppesupporting
confidence: 91%
See 2 more Smart Citations
“…Considering the species list, it was possible to recognize that 98% of species belong to the tribes Scotobiini, Nycteliini and Praociini. This result coincides with that of Kuschel (1969), who identified these tribes as the most representative of the Patagonian steppe, and with those of Sackmann and Flores (2009) and Carrara et al (2011a) who found the dominance of species of these three tribes for small-scale studies within the steppe. The high occurrence of endemic tenebrionids in the Patagonian steppe compared with other close arid biogeographic provinces suggests a role of its environmental history as the primary cause.…”
Section: Endemic Tenebrionids From the Patagonian Steppesupporting
confidence: 91%
“…2). Moreover, the formation of the isthmus generated isolation between the populations of species living inside and outside the peninsula (Carrara et al 2011a), which originated its own fauna of tenebrionids beetles (Carrara et al 2011a;Flores et al 2011).…”
Section: Areas Of Micro-endemism and Hotspotsmentioning
confidence: 99%
See 1 more Smart Citation
“…These insects are known to play a key role in the biological fragmentation of plant resources, in nutrient cycles, and in the diet of other consumer organisms, particularly vertebrates (Pizarro-Araya, 2010;Vidal et al, 2011). In addition, some Tenebrionidae species are used as indicators of climate conditions (Fattorini, 2010) or to identify areas of endemism or hotspots (Pizarro-Araya & Jerez, 2004;Carrara et al, 2011). In this context, the objective of this study is to determine the taxonomic composition and the variations in relative abundance of epigean tenebrionids in the desert portion of the Coquimbo Region's Coastal Matorral (30-32º Lat S), in Chile.…”
Section: Introductionmentioning
confidence: 99%
“…Si bien el conocimiento de los insectos y arácnidos en el noreste de la región patagónica ha mejorado mucho en los últimos años (Dellapé y Cheli, 2007;Carpintero et al, 2008;Cheli, 2009;Ojanguren-Affilastro y Cheli, 2009;Cheli et al, , 2013Cheli et al, , 2016aCheli y Corley, 2010;Carrara et al, 2011;Flores et al, 2011;Martínez, 2013;Martínez Román, 2014;Dellapé et al, 2015;Baldi et al, 2017;Cheli y Martínez, 2017), todos estos antecedentes se refieren exclusivamente a artrópodos de hábitos epigeos. Por el contrario, es muy limitado lo que se sabe acerca de la ecología de los artrópodos que viven asociados al canopeo arbustivo en la porción sur del Monte (Monte Austral).…”
Section: Capítulo 1: Introducción Objetivos E Hipótesisunclassified